A Multicenter Observational Prospective Study of the Preferred Inhaler After a Switch of Therapy in Asthma Patients. Issue 1 (December 2015) - Wille, Sören; Fircks, Holger
Abstract Introduction Poor compliance and incorrect handling of inhaler devices is common among patients with asthma using traditional dry powder inhalers, and patient preference and perception of ease of handling are important. The aim of this study was to determine the proportion of patients preferring the recently introduced Novopulmon® Novolizer® device (Meda, Sweden) compared with their previous inhaler device. Methods An observational study was conducted among 258 asthma patients in Sweden. Patients aged ≥6 years, receiving maintenance treatment with inhaled corticosteroids, and requiring a switch to another inhaler were included. Patients completed a questionnaire regarding the preference, appearance, handling, instructions for use, dose control, and global perception of the inhaler upon switching the device and again after 2 months' use of the new device. Results Patients were aged from 6 to 85 years. Almost all patients (98%) were switched to the Novolizer inhaler. The majority of patients preferred Novolizer versus their previous inhaler: 92.4% [95% confidence interval (CI) 86.0–96.5%] in the 6–12 years age group, 90.9% (95% CI 70.8–98.9%) in the 13–17 years group, and 83.3% (95% CI 74.4–90.2%) among those aged ≥18 years. The results from 10 questions related to the inhalation process and device handling demonstrated that Novopulmon Novolizer was evaluated by patients as superior compared with Turbuhaler® (AstraZeneca), Diskus® (GlaxoSmithKline) and Easyhaler® (Orion);P  < 0.022 for all comparisons. Conclusion Novopulmon Novolizer was determined by patients to be the preferred device compared with previously used devices, and was the patients' preference for continued use. In particular, the Novolizer's audible, visual and sensory feedback mechanisms (that identify whether the correct dose is loaded and administered) and its general ease of use were highly appreciated by asthma patients. Together this makes the Novopulmon Novolizer an ideal first choice inhaler for treatment of asthma, and also for patients who need to switch inhaler. Funding Meda AB.